PRINCIPLES OF SENSE FORMATION IN THE PHILOSOPHICAL FAIRY TALE "PICTOR'S METAMORPHOSES" BY HERMANN HESSE - Megela , Ivan (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
Deep analysis of the fairy tale is presented as a periphrasis of mystery of life, the work is traced back to its inception, symbolic value of images, magical and alchemical transformation of physical matter is depicted. The article considers the fundamental hermetic principle "As above, so below; As within, so without" that suggests that human consciousness creates reality, Eastern worldview is combined with the principle of active imagination by C. G. Jung as a way to develop self-understanding through the work with symbols and the use of a dynamic language of allegory and parable. The article examines creative principle of synchronicity performed as a metaphor and as the one that arranges events not only by "non-physical" (non-causal) mechanisms but on the basis of their sense. The meanings of psychoanalytic symbols are identified: the carbuncle crystal, the biblical serpent, the "tree of life", the fairy-tale bird.________________References• Bor, Nils. Atomnaya fizika i chelovecheskoe poznanie (Moskva, Izdatelstvo inostrannoj literatury, 1961).• Gavrilina, N. A. «Process razvertyvaniya kak osnovnoj mehanizm simvolizacii obraza (na materiale maloj prozy G. Gesse).» Vestnik Samarskogo gosudarstvennogo universiteta, Seriya «Literatura. Literaturovedenie. Narodnoe tvorchestvo» (2010), dostup https://cyberleninka.ru/.../protsess-razvertyvaniya-kak-osnovnoy-mehanizm-simvoliza• Gejzenberg, V. Fizika i filosofiya. Chast i celoe (Moskva, Nauka, 1999).• Grof, S. Holotropnoe soznanie. Tri urovnya chelovecheskogo soznaniya i ih vliyanie na nashu zhizn (Moskva, Izdatelstvo «AST», 2003), 272.• Gesse, G. «Nochnye igry.» Sobranie Sochinenij v 8 t., tom 7 (Moskva, Izdatelskaya gruppa «Progress- Litera», Harkov, Folio, 1993): 316–321.• Gesse, G. «Hudozhnik i psihoanaliz.» Sobranie Sochinenij v 8 t., tom 8 (Moskva, Izdatelskaya gruppa «Progress- Litera», Harkov, Folio, 1995).• Kopejkin, K. V. «Dushi» atomov i «atomy» dushi Volfgang Ernst Pauli, Karl Gustav Yung i «tri velikih problem fiziki», dostup https://ufn.ru/tribune/trib151208.pdf• Menskij, M. B. Chelovek i kvantovyj mir: Fryazino: «Vek 2» (2005).• Moyo znakomstvo s Germanom Gesse, Apokrif dostup apokrif93.com/blog/2010/08/01/moyo-znakomstvo-s-germanom-gesse/• Mushelishvili, N. L., Sergeev, V. M. «Konteksnaya semantika ponyatij i zarozhdenie logicheskih paradigm (Logika vizantijskih m yslitelej i idei kvantovoj fiziki).» Tekst: semantika i struktura (Moskva, Nauka 1983), 287.• Otto, R. Svyashennoe. Ob irracionalnom v idee bozhestvennogo i ego sootnoshenii s racionalnym (Saknt-Peterburg, ANO, Izdatelstvo SPB universiteta, 2008).• Petrouz, Rodzhers. Put realnosti, ili Zakon, upravlyayushij Vselennoj (Moskva, Izdatelstvo Regulyarnaya i haoticheskaya dinamika. Institut kompyuternyh issledovanij, 2007).• Tresidder, Dzh. Slovar simvolov, per. s angl. S. Palko (Moskva, FAIR-PRESS, 2001), 293.• Franc Mariya Luiza fon. Psihologiya skazki. Tolkovanie volshebnyh skazok, dostup https://www.livelib.ru/.../about-psihologiya-skazkitolkovanie-volshebnyh-skazok-psih.• Yung, K. G. Vospominaniya, snovideniya, razmyshleniya (Kiev, Airland, 1994), 377.• Yung, K. G. Sinhronichnost :kauzalnyj obedinyayushij princip (Moskva, Refl-buk, Kiev, Vakler, 1999).• Hesse, H. Brief an F.Abel. Baden. Dezember 1931 (Suhrkamp Verlag Berlin und Frankfurt am Main, 10 bis 12 Auflage, 1984), 81.• Hesse, H. Die Märchen (Suhrkamp. Taschenbuch. Erste Auflage-Frankfurt am Main): 206, 210–211.• Hesse Hermann. Sämtliche Werke, Band9: Die Märchen, Legenden, Übertragungen, Dramatisches, Idyllen, Hrsg. v. Volker Michels (Frankfurt a.M., Suhrkamp 2002): 634.• Hesse, Hermann. Sonne und Mond seie4n freundlich zu Ihnen, liebe Freundin. Der Briefwechsel mit Anny und Hermann Bodner, Hrsg von Jurgen Bellow (Hamburg, Igel Verlag, 2013): 134.• Franz Marie Louise von. Psychologische Märcheninterpretation (Eine Einfuhrung, Mǖnchen, 1986).• Freud Sigmund. «Der Dichter und das Phantasieren.» Methoden der Literaturanalyse im20 (Jahrhundert. Frankfurt a. Main; Berlin. Munchen, Verlag Moritz Diesterweg, 1974): 8–14.• Neue Schweizer Rundschau (Januar, 1955).• Padularosa/ Daniela Hermann Hesse-Wanderer der inneren Welt. Die Therapie der Psyche und die Darstellung der Natur in den Marchen und Aquarellen / Magischer Einklang. Dialog der Künste im Werk Hermann Hesses, Hrsg von Herriette Herwig und Sikander Singy (Wallstein Verlag Göttingen, 2011).